Structural Optimization of Oxide/Metal/Oxide Transparent Conductors for High‐Performance Low‐Emissivity Heaters. Issue 24 (15th October 2018) - Li, Peng; Li, Huapeng; Ma, Jiangang; Zhou, Yu; Zhang, Wei; Cong, Lujia; Xu, Haiyang; Liu, Yichun
Abstract: Oxide/metal/oxide transparent conductors (TCs) have attracted increasing interest in response to demands of explosively developing flexible optoelectronic devices. Fabricating continuous ultrathin metal films on supporting oxides is an unsolved conundrum due to Volmer–Weber growth. Instead of introducing a nucleation inducer, which generally results in inferior optical‐electrical performances, an oxygen plasma treatment‐assisted method is used to prepare Al‐doped ZnO/Ag/Al‐doped ZnO (AZO/Ag/AZO) TCs. Experimental results evidence that increasing surface energy and adhesion of the supporting AZO film allows the formation of a continuous Ag film as thin as 6 nm. The oxygen plasma treatment successfully suppresses the Volmer–Weber and improves the visible transmission, infrared reflectance, and conductivity of the AZO/Ag/AZO TCs. Furthermore, thicknesses of the AZO films in AZO/Ag/AZO TCs are elaborately optimized by using finite‐difference time‐domain method to balance the transmittance and reflectance. The resulting AZO/Ag/AZO TCs are incorporated in low‐emissivity heaters that exhibit high visible transmittance (93.6%@550 nm), high infrared reflectance (67%@1500 nm), low sheet resistance (5.6 Ω □ −1 ), and low operating voltage (5 V). These results offer valuable insight into the role of oxygen plasma treatment in altering the metal growth mode on oxide surfaces, these structural optimization methods can be extended to the development of oxide/metal/oxide‐based electronics. Abstract : Structure of oxide/metal/oxide transparent conductors is optimized by using oxygen plasma treatment and finite‐difference time‐domain method simulation to obtain low‐emissivity heaters with high visible transmittance, high infrared reflectance, as well as low sheet resistance. Valuable insight into the role of oxygen plasma treatment in altering the metal growth mode on oxide surfaces is offered.